Potensi Daun Sirsak (Annona Muricata L.) sebagai Kandidat Fungisida Nabati Penghambat Pertumbuhan Cendawan Patogen Colletotrichum Gloeosporioides - Syayyidah Fatimatuz Zahro; Lailatul Restuning Putri Istiqomah; Galuh Citra Cahya Rohmana; Denise Ayu Yustikaningrum; Christyfani Sindhuwati (Universitas Andalas, 2023)
The attack of the Colletotrichum gloeosporioides fungus causes losses to farmers. The prolonged use of synthetic fungicides to treat this fungus harms the environment and consumers. Soursop leaves (Annona muricata L.) contain antioxidant compounds that act as antifeedants, contact poisons, and stomach poisons for plant pests and can potentially become a vegetable fungicide as a growth inhibitor for Colletotrichum gloeosporioides in postharvest horticulture. This study used a multilevel extraction method with solvents of n-hexane, ethyl acetate, and 95% ethanol. Tests for the content of secondary metabolites of soursop leaf extract in the form of alkaloids, flavonoids, saponins, and tannins were carried out qualitatively and quantitatively using a UV-Vis Shimadzu 1800 spectrophotometer. The inhibition test of the extract against the fungus Colletotrichum gloeosporioides was carried out using disc paper soaked with soursop leaf extract for a certain time. The qualitative test results of soursop leaf extract showed that it contained alkaloids, flavonoids, saponins, and tannins. The fungal inhibition zone test showed the most optimal results on soursop leaf extract with a long extraction time of 144 hours and a content of 50%, indicated by the largest diameter of the inhibition zone against the fungus Colletotrichum gloeosporioides, namely 1.7 cm.